Facile preparation of NPs based on Ag–AgCl immobilized in porous PVA sphere with high visible light photoactivity and good photostability under Cl− condition. Issue 1 (March 2016) - Chen, XingYu; Hou, JiaoJiao; Yang, Hu; Xu, Zhen-Liang
Highlights: Synthesis of NPs based on Ag–AgCl immobilized in porous PVA sphere. The AgCl/PVA sphere has a high photoactivity and a good photostability. The possible mechanism of photocatalysis was proposed. Abstract: Porous PVA sphere immobilized with nanoparticles (NPs) based on Ag–AgCl was synthesized for the first time. The approach can be simply divided into three steps. Firstly the in-situ synthesis of Ag NPs in PVP/N, N -dimethylacetamide (DMAc) solution, secondly the phase inversion of Ag NPs/PVA aqueous solution in acetone (AC) to get porous Ag/PVA sphere, finally the crosslinking of Ag/PVA porous sphere by glutaraldehyde using HCl as catalyst, and AgCl NPs were formed through the reaction between Ag NPs and HCl simultaneously. BET and SEM results showed that AgCl/PVA sphere had a porous structure, and its surface area was about 192 m 2 /g. XRD and XPS data proved the formation process of NP from Ag ions to Ag NPs and then to AgCl NPs. TEM and EDX images revealed that AgCl NPs were mainly buried inside PVA matrix and their sizes were about 50–90 nm. Even for 5th cycles of photodegradation of methyl orange (MO) in xenon lamp, AgCl/PVA porous sphere still showed a high photoactivity and a good photostability in the presence of chloride ions. The possible mechanism of photocatalysis was proposed finally.